2016
DOI: 10.14814/phy2.13055
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging decreases endothelin‐1 excretion and glomerular albumin permeability during type 1 diabetes

Abstract: Increased renal endothelin‐1 (ET‐1) production and an ETA receptor‐dependent increase in glomerular albumin permeability (Palb) accompany type 1 diabetes mellitus (T1D). We hypothesized that T1D‐induced oxidative stress contributes to renal ET‐1 production and glomerular Palb. Male rats with streptozotocin‐induced T1D were provided free access to drinking water without additives (T1D rats) or containing the free radical scavenger tempol (1 mmol/L; T1D+Tempol). After 3 weeks, T1D+Tempol rats displayed lower uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
9
0
3
Order By: Relevance
“…Additionally, superoxide anions appear to stimulate the production of TXA2 and 8-isoprostane, an equipotent agonist of TP [52, 62] and ET-1 [63, 64]. Thus, pharmacological strategies such as pleiotropic drugs to interrupt this vicious cycle cascade seem to be relevant against AT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, superoxide anions appear to stimulate the production of TXA2 and 8-isoprostane, an equipotent agonist of TP [52, 62] and ET-1 [63, 64]. Thus, pharmacological strategies such as pleiotropic drugs to interrupt this vicious cycle cascade seem to be relevant against AT.…”
Section: Discussionmentioning
confidence: 99%
“…Increased proteinuria and albuminuria in diabetic animals are associated with structural protein impairment and glomerular permeability induced by hyperglycemia. 41,42 However, physical exercise prevented the increase of proteinuria and serum creatinine in the rats of the OTD group. In a prior study from our laboratory, aerobic exercise performed pre and postinduction of DM reduced proteinuria in nonovariectomized diabetic rats.…”
Section: Discussionmentioning
confidence: 94%
“…However, exercise training prevented the urinary excretion of proteins in OTD group rats. Increased proteinuria in diabetic animals may be associated with structural protein impairment and glomerular permeability triggered by hyperglycemia (Ito et al, 2015, Wang et al, 2015, Saleh et al, 2016. While beneficial effects of exercise were attributed to the reduction of hyperglycemia, proteinuria and albuminuria, improved bioavailability of nitric oxide and reduction of oxidative stress (Albright et al, 1995;Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia induces an increase in reactive oxygen species (ROS) and changes in renal structure, suggesting that this may be associated with the development of renal lesions (Mansouri et al, 2011;Punaro et al, 2014;Fernandes et al, 2016). Saleh et al (2016) demonstrated that antioxidant treatment reduced urinary excretion of TBARS, endothelin 1 and glomerular superoxide production, in rats with DM1 induced by estreptozotocin (STZ).…”
Section: Introductionmentioning
confidence: 99%